2006
DOI: 10.1038/emm.2006.38
|View full text |Cite
|
Sign up to set email alerts
|

Association between excision repair cross-complementation group 1 polymorphism and clinical outcome of platinum-based chemotherapy in patients with epithelial ovarian cancer

Abstract: ERCC1 is a DNA repair gene and has been associated with resistance to DNA damaging agents. In this study we hypothesized that a polymorphism of ERCC1 Asn118Asn (C→T) might affect the platinum-resistance of epithelial ovarian cancer patients to platinum-taxane chemotherapy administered postoperatively. Using the SNapShot assay, we assessed this polymorphism in ERCC1 in 60 ovarian cancer patients. Platinum-resistance was defined as progression on platinum-based chemotherapy or recurrence within 6 months of compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 14 publications
5
68
2
1
Order By: Relevance
“…Consistent with previous studies regarding the C/C genotype and its relationship with poor treatment response (38), these authors found that ovarian cancer patients harboring C/C genotypes were less responsive to chemotherapy and maintained a higher risk for disease progression and death in contrast to those harboring C/T or T/T genotypes. Findings of Smith et al showed that ovarian cancer patients with a high ERCC-1 expression or the C/C genotype at codon 118 may benefit from a platinum/ paclitaxel combination, whereas patients with a low ERCC-1 expression or the C/T or T/T genotype may respond well to platinum without paclitaxel.…”
Section: Mthfr C677t Polymorphism and Methotrexatesupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with previous studies regarding the C/C genotype and its relationship with poor treatment response (38), these authors found that ovarian cancer patients harboring C/C genotypes were less responsive to chemotherapy and maintained a higher risk for disease progression and death in contrast to those harboring C/T or T/T genotypes. Findings of Smith et al showed that ovarian cancer patients with a high ERCC-1 expression or the C/C genotype at codon 118 may benefit from a platinum/ paclitaxel combination, whereas patients with a low ERCC-1 expression or the C/T or T/T genotype may respond well to platinum without paclitaxel.…”
Section: Mthfr C677t Polymorphism and Methotrexatesupporting
confidence: 87%
“…Another study on ovarian cancer patients has stressed the association between the C/C genotype and increased resistance to platinum-based chemotherapy, consistent with a higher transcription activity of the AAC codon (38).…”
Section: Mthfr C677t Polymorphism and Methotrexatementioning
confidence: 90%
“…It is possible that a decreased level of ERCC1 mRNA expression influences the repair efficiency of DNA damage, which then contributes to cancer susceptibility. Studies have also shown an association between the polymorphism and malignancies such as lung, ovarian and colorectal cancer (26)(27)(28)(29), although no previous association with cervical cancer has been shown. Our study showed that ERCC1 118C>T may be a potential risk factor for SCC.…”
Section: Cin Scc Cin Scc --------------------------------------------mentioning
confidence: 99%
“…We assume that these differences were due to the absence of larger studies. Which genotype is associated with higher mRNA levels and/or better prognosis with the patients that received platinum compound is still a controversial topic (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Some reported environmental factors such as smoking interaction might modulate and mask the genetic effect of polymorphism (35)(36)(37).…”
Section: Responder/global -------------------------------------------mentioning
confidence: 99%
“…Since Yu et al, reported that ERCC1 mRNA levels were reduced in human ovarian cancer cells with a variant allele, and that those cells were inferior in recovery from platinum damage to cells with wild-type allele (21), several studies have assessed the relation between ERCC1 codon 118 polymorphism and sensitivity to a platinum agent in ovarian cancers, colorectal cancers, gastric cancers, and non-small cell lung cancers (22)(23)(24)(25)(26)(27)(28)(29)(30)(31). It is possible for ERCC1 codon 118 polymorphism to be a biomarker for assessing the sensitivity to a platinum-based therapy, although it is still a matter of controversy whether either a wild-type allele or a mutant-type allele affect the platinum resistance.…”
Section: Introductionmentioning
confidence: 99%